Using Scratch in mathematics education: a pedagogical experience with students in the mathematics education program - Silva, Felipe Queiroz da (2024)
This text presents a report of an experience applying activities related to Computational Thinking and Creative Programming using Scratch in two classes from the third semester of a Mathematics Teaching degree course. It describes the activities conducted, the points raised and discussed among the students, as well as the gains and difficulties pointed out by them. Our objective is to answer the question: What are the gains and difficulties found in the use of Scratch with students in the Mathematics teaching degree course? For data collection, in addition to transcripts of the meeting recordings, forms were applied before and after the activities. Through their analysis, the importance of a solid and continuous training in technological resources for future educators in the modern educational context can be observed. We conclude by emphasizing that training for the use of Scratch in mathematics teaching can not only expands the range of available pedagogical resources but also promotes a more dynamic and engaging learning environment.